Organic system evaluation of cassava varieties in the humid tropics of South India: agronomic, nutritional, quality, economic and soil health indicators - G. Suja; J. Sreekumar; S. J. Harishma; G. Byju; S. S. Veena; M. N. Sheela; S. Sunitha; A. N. Jyothi; D. Jaganathan; N. Ravisankar; C. S. Sooraj (Organic Agriculture, 2026)

Low-Dose Cannabidiol Treatment does not Alter Cognitive Performance in the HIV-1 Transgenic Rat Model of NeuroHIV - Samantha M. Ayoub; Sunitha Vemuri; Arpi Minassian; Jared W. Young (Journal of Neuroimmune Pharmacology, 2026)

Seasonal Hydrogeochemical and Geospatial Assessment of Agro-Geogenic Groundwater Contamination in Mining-Influenced Terrain, SW Y.S.R. Kadapa District, A.P., India - Y. Sudharshan Reddy; V. Sunitha; B. Suvarna; M. Prasad; G. Chennakesava Reddy (Water, Air, & Soil Pollution, 2026)

Physics-Guided Deep Learning with Bayesian Optimization for Enhanced River Streamflow Prediction - D. Suresh; M. Sahaya Sheela; Pamarthi Sunitha; S. Gopalakrishnan (Water Resources Management, 2026)

OsHV-1 Promoter-driven Transgene Expression in Bivalve Cells: An In Vitro Study with an EGFP-tagged Oncogenic H-RasV12 - Soumya Balakrishnan; Ambadi Kannan Maliyekkal Sajeevan; R. Namitha; M. R. Sunitha; A. Muneer; I. S. Bright Singh; Jayesh Puthumana (Environmental Management, 2025)

Optimizing YOLO models for high-accuracy automated detection and classification of road surface distresses - M. Manjusha; V. Sunitha (Innovative Infrastructure Solutions, 2025)

Evaluating geostatisical approaches and their integration with pedotransfer functions for estimating the spatial distribution of cation exchange capacity - Farag M. A. Altalbawy; Merwa Alhadrawi; Ashok Kumar Bishoyi; Subbulakshmi Ganesan; Aman Shankhyan; S. Sunitha; Anita Devi; Rajashree Panigrahi; Rubyat Alam (Environmental Monitoring and Assessment, 2025)

Estimation of YOLO algorithms for extracting traffic data using UAV and stationary camera - M. Manjusha; R. Niveditha; V. Sunitha (Innovative Infrastructure Solutions, 2025)

Chandra’s surface thermophysical experiment (ChaSTE) onboard Chandrayaan 3 Lander - Nizy Mathew; K. Durga Prasad; Dinakar Prasad Vajja; V. Aasik; Fazil Mohammad; P.P. Pramod; M. Satheesh Chandran; Kiran John Antony; M. Ram Prabhu; M.B. Dhanya; Manu V. Unnithan; Shiju G. Thomas; et al. (Advances in Space Research, 2025)

Microfibers release during washing and, removal by tamarind fruit shell carbon filters: Subsequent utilization in crystal violet dye removal from water - M. Prabhakaran; T.G. Sunitha; Kiyoshi Omine; V. Sivasankar (Process Safety and Environmental Protection, 2025)

Genetic enhancement of reproductive stage drought tolerance in RPHR-1005R and derivative rice hybrids through marker-assisted backcross breeding in rice (Oryza sativa L.) - N. Sravanraju; P. Beulah; V. Jaldhani; P. Nagaraju; A. S. HariPrasad; P. Brajendra; N. Sunitha; R. M. Sundaram; P. Senguttuvel (Molecular Biology Reports, 2024)

Socioeconomic Changes Based Climate Training for Agricultural Application Using Deep Learning Model - M. Sunitha; M. Durairaj; A. Rajalingam; Siti Khalidah Mohd Yusoff; S. Hari Chandra Prasad; S. N. Lakshmi Malluvalasa; Ajmeera Kiran (Remote Sensing in Earth Systems Sciences, 2024)

Multitrait engineering of Hassawi red rice for sustainable cultivation - Khalid Sedeek; Nahed Mohammed; Yong Zhou; Andrea Zuccolo; Krishnaveni Sanikommu; Sunitha Kantharajappa; Noor Al-Bader; Manal Tashkandi; Rod A. Wing; Magdy M. Mahfouz (Plant Science, 2024)

Revisiting population genetics with new genomic resources in dolichos bean (Lablab purpureus L. Sweet): an orphan crop - Vinayak Spoorthi; S. Ramesh; N. C. Sunitha; C. Anilkumar; M. S. Vedashree (Genetic Resources and Crop Evolution, 2024)

Arctic–midlatitude–tropics interactions in January 2020: linkages to precipitation extremes over Indian region - S. D. Sanap; M. Mohapatra; D. R. Pattanaik; S. Sunitha Devi; Satendra Kumar; A. Kashyapi (Meteorology and Atmospheric Physics, 2024)

Focused identification of germplasm strategy (FIGS): a strategic approach for trait-enhanced pre-breeding - N. C. Sunitha; M. D. Prathibha; R. Thribhuvan; B. M. Lokeshkumar; P. S. Basavaraj; H. C. Lohithaswa; C. Anilkumar (Genetic Resources and Crop Evolution, 2024)

Groundwater quality assessment using multivariate statistical approach and geospatial modelling around cement industrial corridor, South India - B. Suvarna; V. Sunitha; Y. Sudharshan Reddy; B. Muralidhara Reddy; A. K. Kadam; M. Ramakrishna Reddy (International Journal of Environmental Science and Technology, 2023)

Federated Analysis in COINSTAC Reveals Functional Network Connectivity and Spectral Links to Smoking and Alcohol Consumption in Nearly 2,000 Adolescent Brains - Harshvardhan Gazula; Kelly Rootes-Murdy; Bharath Holla; Sunitha Basodi; Zuo Zhang; Eric Verner; Ross Kelly; Pratima Murthy; Amit Chakrabarti; Debasish Basu; Subodh Bhagyalakshmi Nanjayya; Rajkumar Lenin Singh; et al. (Neuroinformatics, 2023)

The water footprint of root and tuber crops - S. Sunitha; A. U. Akash; M. N. Sheela; J. Suresh Kumar (Environment, Development and Sustainability, 2023)

Pollutant removal from cheese processing effluent using effective indigenous natural scavengers - B. Sowmiya Rajalakshmi; A. Annes silva fathima; B. Sunitha Jasmine; M. Vasanthy; C. Thamarai Selvi; Rajinikanth Rajagopal; Ramsha Khan; Ashraf Atef Hatamleh; Bassam Khalid Alnafisi; Mansour K. Gatasheh; Soon Woong Chang; Balasubramani Ravindran (Environmental Monitoring and Assessment, 2023)

Yield Estimation of Cassava Using SIMCAS Model Over the Major Cassava Growing Regions in India - Divya K. Lekshmanan; Raji Pushpalatha; V. S. Santhosh Mithra; S. Sunitha; James George; M. Velmurugan; P. Ashok; N. V. Mhasker; K. D. Desai; R. Shiny; Gangadharan Byju (Agricultural Research, 2022)

Genetic stock identification in Perna viridis (Linnaeus1758) from the Indian Peninsula by using microsatellite markers - P. R. Divya; Linu Joy; Sunitha Poulose; P. M. Elizabeth Jency; V. S. Basheer; A. Kathirvelpandian; Vindhya Mohindra; Kuldeep Kumar Lal (Molecular Biology Reports, 2022)

Impact of climate change on the yield of tropical root and tuber crops vs. rice and potato in India - Raji Pushpalatha; VS Santhosh Mithra; S Sunitha; James Goerge; M Nedunchezhiyan; K Mamatha; P Ashok; Sheriful Alam; BK Saud; J Tarafdar; Surajit Mitra; Chandra Deo; et al. (Food Security, 2022)

ENIGMA + COINSTAC: Improving Findability, Accessibility, Interoperability, and Re-usability - Jessica A. Turner; Vince D. Calhoun; Paul M. Thompson; Neda Jahanshad; Christopher R. K. Ching; Sophia I. Thomopoulos; Eric Verner; Gregory P. Strauss; Anthony O. Ahmed; Matthew D. Turner; Sunitha Basodi; Judith M. Ford; et al. (Neuroinformatics, 2022)
The FAIR principles, as applied to clinical and neuroimaging data, reflect the goal of making research products F indable, A ccessible, I nteroperable, and R eusable. The use of the Collaborative Informatics and Neuroimaging Suite Toolkit for Anonymized Computation (COINSTAC) platform in the Enhancing Neuroimaging Genetics through Meta-Analysis (ENIGMA) consortium combines the technological approach of decentralized analyses with the sociological approach of sharing data. In addition, ENIGMA + COINSTAC provides a platform to facilitate the use of machine-actionable data objects. We first present how ENIGMA and COINSTAC support the FAIR principles, and then showcase their integration with a decentralized meta-analysis of sex differences in negative symptom severity in schizophrenia, and finally present ongoing activities and plans to advance FAIR principles in ENIGMA + COINSTAC. ENIGMA and COINSTAC currently represent efforts toward improved Access, Interoperability, and Reusability. We highlight additional improvements needed in these areas, as well as future connections to other resources for expanded Findability.

Evaluation of heavy rainfall warnings of India National Weather Forecasting Service for monsoon season (2002–2018) - M Mohapatra; Naresh Kumar; Krishna Mishra; Sunitha Devi (Journal of Earth System Science, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Protective effect of (+)–catechin against lipopolysaccharide-induced inflammatory response in RAW 264.7 cells through downregulation of NF-κB and p38 MAPK - M. A. Sunil; V. S. Sunitha; Prasanthkumar Santhakumaran; Mohind C. Mohan; Midhun Sebastian Jose; E. K. Radhakrishnan; Jyothis Mathew (Inflammopharmacology, 2021)

Quality criteria for groundwater use from a rural part of Wanaparthy District, Telangana State, India, through ionic spatial distribution (ISD), entropy water quality index (EWQI) and principal component analysis (PCA) - N. Subba Rao; B. Sunitha; N. Adimalla; M. Chaudhary (Environmental Geochemistry and Health, 2020)

ADAPTATION TO CLIMATE CHANGE: IMPACT OF CAPACITY BUILDING, INDIA - Krishna Reddy Kakumanu; Yella Reddy Kaluvai; M. Balasubramanian; Udaya Sekhar Nagothu; Gurava Reddy Kotapati; Sunitha Karanam (Irrigation and Drainage, 2019)
Climate change adversely affects the determinants of agriculture. Adaptation serves as an important strategy to reduce the adverse effects of climate change (variability) and vulnerability of the people. Adaptation through an innovation programme was implemented for 4 years during 2012–2016 to improve the adaptive capacity in agriculture and the water sectors through capacity building and implementation in the Krishna River Basin, India. Primary data were collected from 178 farm households of the Nagarjuna Sagar Project command area covering both adopters and non‐adopters of water‐saving interventions from the study area. The double difference method was used to analyse the impact of adaptation through capacity building and implementation. The water‐saving interventions include alternate wetting and drying (AWD) in rice, a modified system of rice intensification (MSRI) and direct seeding of rice (DSR). The capacity building and water saving increased crop yields by 0.96, 0.93 and 0.77 t ha −1 through AWD, MSRI and DSR respectively. The three practices have increased farmers’ income and decreased the cost of cultivation in DSR by Rs.11 000 (US$169) ha −1 . The methods can be more focused in canal commands on a larger scale for equal distribution of water to all the head, middle and tail‐end regions. © 2018 John Wiley & Sons, Ltd.

Role of enhanced synoptic activity and its interaction with intra-seasonal oscillations on the lower extended range prediction skill during 2015 monsoon season - S. Abhilash; R. Mandal; A. Dey; R. Phani; S. Joseph; R. Chattopadhyay; S. De; N. K. Agarwal; A. K. Sahai; S. Sunitha Devi; M. Rajeevan (Climate Dynamics, 2018)

Population genomics of dengue virus serotype 4: insights into genetic structure and evolution - Vaishali P. Waman; Sunitha Manjari Kasibhatla; Mohan M. Kale; Urmila Kulkarni-Kale (Archives of Virology, 2016)

Removal of heavy metals from tannery effluents of Ambur industrial area, Tamilnadu by Arthrospira (Spirulina) platensis - S. Balaji; T. Kalaivani; C. Rajasekaran; M. Shalini; S. Vinodhini; S. Sunitha Priyadharshini; A. G. Vidya (Environmental Monitoring and Assessment, 2015)

Synthesis, Characterization, Antimicrobial, DNA Binding and Cleavage Studies of Mixed Ligand Cu(II), Co(II) Complexes - D. Shiva leela; B. Ushaiah; G. Anupama; M. Sunitha; C. Gyana Kumari (Journal of Fluorescence, 2015)

Viper venom-induced oxidative stress and activation of inflammatory cytokines: a therapeutic approach for overlooked issues of snakebite management - M. Sebastin Santhosh; M. Shanmuga Sundaram; K. Sunitha; K. Kemparaju; K. S. Girish (Inflammation Research, 2013)

Calorimetric investigation of copper(II) binding to Aβ peptides: thermodynamics of coordination plasticity - Cristina Sacco; Rachel A. Skowronsky; Sunitha Gade; John M. Kenney; Anne M. Spuches (JBIC Journal of Biological Inorganic Chemistry, 2012)

An overview on genus garcinia: phytochemical and therapeutical aspects - M. Hemshekhar; K. Sunitha; M. Sebastin Santhosh; S. Devaraja; K. Kemparaju; B. S. Vishwanath; S. R. Niranjana; K. S. Girish (Phytochemistry Reviews, 2011)

Zooplankton community structure across an eddy-generated upwelling band close to a tropical bay-mangrove ecosystem - M. Rakhesh; A. V. Raman; C. Kalavati; B. R. Subramanian; V. S. Sharma; E. Sunitha Babu; Nanduri Sateesh (Marine Biology, 2008)